2019
DOI: 10.1002/bab.1817
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of penicillin G acylase immobilized on glutaraldehyde‐modified titanium dioxide

Abstract: In this work, TiO2, which was modified by glutaraldehyde, was adopted as the carrier; the penicillin G acylase (PGA) was immobilized and the influence of immobilized conditions, such as pH of solution, the concentration of PGA, the immobilization temperature, and the reaction time, on the catalytic performance of the immobilized PGA was investigated and optimized. During this process, potassium penicillin G (PG) was chosen as substrate, and the quantity of 6‐aminopenicillanic acid (6‐APA) produced by PG at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…While EA and EAR exhibited a quite opposite trend, and a maximum was obtained at pH = 8.0. The variation of ELC could be ascribed to the Schiff base reaction between amino and aldehyde group; it was a nucleophilic addition reaction, 37 and was affected seriously by the pH of reaction media. In the acidic condition, the protonated aldehyde groups would enhance the electrophilicity of amino groups and immobilize easily 38 .…”
Section: Resultsmentioning
confidence: 99%
“…While EA and EAR exhibited a quite opposite trend, and a maximum was obtained at pH = 8.0. The variation of ELC could be ascribed to the Schiff base reaction between amino and aldehyde group; it was a nucleophilic addition reaction, 37 and was affected seriously by the pH of reaction media. In the acidic condition, the protonated aldehyde groups would enhance the electrophilicity of amino groups and immobilize easily 38 .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 4, laccase immobilized on supports based on TiO 2 or ZnO has been used to remove various dyes (for example: Alizarin Red S, Remazol Brilliant Blue R, Malachite Green, Crystal Violet, Acid Blue etc.) [34][35][36][37]. Those dyes were removed with 60-90% efficiency.…”
Section: Decolorization Of Organic Dyes By the Tio 2 /Zno/ltv Biocatalytic Systemmentioning
confidence: 99%
“…In another study, TiO 2 modified with different micro-environments was used as a carrier for penicillin G acylase (PGA) immobilization. The results demonstrated that the functional groups and arm-length of the immobilization sites of the titania had a good influence on the enzymatic yield of immobilized PGA [37]. Liu et al [38] used lipase immobilized onto Fe 3 O 4 /TiO 2 nanoparticles by electrostatic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…PGA played an important biocatalyst and catalyzed the reaction of penicillin G (PG) potassium salt in semi-synthetic antibiotics to form 6aminopenicillinc acid (6-APA) and other semi-synthetic penicillins. [35][36][37][38] because the reaction under the catalytic of PGA would take place at mild and environmental friend conditions while with high production. In the application process, the effective recovery and recycle of PGA was always a necessary requirement because of economic consideration.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the study, Fe 3 O 4 @SiO 2 used as an enzyme immobilization carrier received particular attention leading to specific magnetic susceptibility, lower toxicity, and synthetic-modifying surface [ 24 34 ]. PGA played an important biocatalyst and catalyzed the reaction of penicillin G (PG) potassium salt in semi-synthetic antibiotics to form 6-aminopenicillinc acid (6-APA) and other semi-synthetic penicillins [ 35 38 ] because the reaction under the catalytic ofPGA would take place at mild and environmentally friendly conditions at high production. In the application process, theeffective recovery and recycle of PGA was always a necessary requirement economically.…”
Section: Introductionmentioning
confidence: 99%